2010
DOI: 10.1176/foc.8.3.foc398
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Sensitivity to the Environment: The Case of the Serotonin Transporter Gene and Its Implications for Studying Complex Diseases and Traits

Abstract: Evidence of marked variability in response among people exposed to the same environmental risk implies that individual differences in genetic susceptibility might be at work. The study of such Gene-by-Environment (GxE) interactions has gained momentum. In this article, the authors review research about one of the most extensive areas of inquiry: variation in the promoter region of the serotonin transporter gene (SLC6A4; also known as 5-HTT) and its contribution to stress sensitivity. Research in this area has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
420
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(443 citation statements)
references
References 155 publications
17
420
2
4
Order By: Relevance
“…The leading explanation for this variability proposes that genetic variance modulates the effect of stress on the brain (9;10). Indeed, numerous studies have shown that persons with a specific genetic make-up are more prone to develop stress-related mental disorders after experiencing major life events like CA (11)(12)(13). Moreover, recent studies suggest that gene by stress interactions may be involved in inter-individual differences in local brain volume (14) and may also play a role in the onset of several psychiatric disorders, like bipolar disorder, schizophrenia, attention deficit hyperactivity disorder and depression (for review see (15)).…”
Section: Introductionmentioning
confidence: 99%
“…The leading explanation for this variability proposes that genetic variance modulates the effect of stress on the brain (9;10). Indeed, numerous studies have shown that persons with a specific genetic make-up are more prone to develop stress-related mental disorders after experiencing major life events like CA (11)(12)(13). Moreover, recent studies suggest that gene by stress interactions may be involved in inter-individual differences in local brain volume (14) and may also play a role in the onset of several psychiatric disorders, like bipolar disorder, schizophrenia, attention deficit hyperactivity disorder and depression (for review see (15)).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, research has found evidence of GxE interaction, suggesting genetic effects on a variety of measures (e.g., depression, college attendance) depend on our environment (Caspi et al 2003;Guo et al 2008;Shanahan et al 2008;Thapar et al 2007;Caspi et al 2010). Replication of GxE effects have often proved elusive (see Dick 2011 and Manuck and McCaffery 2014 for reviews).…”
Section: Gene-environment Interactionmentioning
confidence: 99%
“…One important prerequisite for candidate G 9 E is its biological plausibility, that is, genes and environment are convergent to one biological pathway underlying the focused psychopathology (Caspi et al 2010;Moffitt et al 2006;Rutter et al 2009). Biological plausibility for the present research resides in the joint effect of BDNF Val66Met and parenting on abnormal BDNF functioning, which has been shown to be involved in depression (CastrĂ©n and RantamĂ€ki 2010).…”
Section: Biological Plausibility Of Bdnf Val66met 3 Parentingmentioning
confidence: 99%